Targeted treatment of hepatocellular carcinoma with aptamer-guided solid lipid nanoparticles loaded with norcantharidin - Yilin Xu; Min Wang; Jing Wu; Manshu Zou; Donghai Wu; Jing Gong; Pingjie Wang; Hong Yan; Xinhua Xia (Drug Delivery)
Liver cancer is a common malignancy in the world, and its incidence and mortality rate are increasing year by year. The disease has a short course and a high mortality rate, posing a serious threat to humanity and health. The objective of this study is to create novel liver-targeted nanoparticles as a potential treatment for liver cancer. The aptamer (APS613-1) modified redox-sensitive norcantharidin solid lipid nanoparticles (Apt-PEG2000-ss-NCTD-SLNs) were prepared by emulsified ultrasonic dispersion method and characterized. The tumor targeting, antitumor effect and safety of the nanoparticles were investigated and evaluated in vitro and in vivo. The particle size of Apt-PEG2000-ss-NCTD-SLNs was 87.95 ± 3.32 nm, and the encapsulation efficiency was about 80.74 ± 2.36%, which had good biocompatibility. The results of in vitro experiments showed that, compared with unmodified solid lipid nanoparticles (NCTD-SLNs), Apt-PEG2000-ss-NCTD-SLNs had better targeting for liver tumor cells, and a stronger ability to inhibit cell proliferation and migration, as well as promote cell apoptosis. The in vivo results revealed that Apt-PEG2000-ss-NCTD-SLNs demonstrated good safety and anti-tumor efficacy, and its mechanism was achieved through the inhibition of cell proliferation and induction of apoptosis. The functionalized nanoparticles modified by aptamer APS613-1 can be used for the liver-targeted delivery of antitumor drugs for the treatment of liver cancer, and Apt-PEG2000-ss-NCTD-SLN is a potential drug for the treatment of liver cancer.